Konsep 4D (Disconfirmation, Dissatisfaction, Dissonance, Disaffection) dalam Mengevaluasi Kualitas Layanan Pendidikan Tinggi Gendut Sukarno - Sukarno, Gendut (Jurnal Bisnis Indonesia, 2024)
This research intends to examine the conceptual model of the Quality of Educational Servicesprovided by several Private Universities (PTS) in Surabaya by using a review of Disconfirmation,Dissatisfaction, Dissonance, Disaffection in evaluating the quality of educational services in StudyEvaluation and Registration Results Services; Bank Services; Student Services; HealthServices/Polyclinics; Language Center UPT Services; Computer Center Services, and CentralLibrary Services. It is hoped that this study can help leaders of Private Universities (PTS) in makingdecisions to increase and maintain the existence of student enthusiasm and/or graduation. The sampleused in this research was 200 students from 5 (five) state universities, namely: East Java "Veteran"National Development University (UPN), Airlangga University (UNAIR), Sepuluh Nopember Instituteof Technology (ITS), Surabaya State University (UNESA ), Sunan Ampel State Islamic UniversitySurabaya (UINSA). Several tests need to be carried out before the data is processed so that itconforms to the assumptions required by multivariate data analysis (validity and reliability, normality,multicolonierity or singularity). The analytical method used in this research is Structural EquationModeling [SEM], and the measurement model is Confirmatory Factor Analysis [CFA]. By usingAMOS 4.01 the test results show that the Dissatisfaction Concept is eliminated, Dissonance canevaluate from a significantly negative side the Quality of Student Education Services which isacceptable, likewise Disaffection can evaluate from a significantly negative side the Quality ofStudent Education Services which is acceptable. Meanwhile, Disconfirmation can evaluatesignificantly from a negative side that the quality of student services is unacceptable.Keywords: Disconfirmation; Dissastisfaction; Dissonance; Disaffection